Oxaliplatin-Induced Neurotoxic Side Effects and Their Impact on Daily Activities: A Longitudinal Study Among Patients With Colorectal Cancer. Issue 6 (November 2019) - Drott, Jenny; Fomichov, Victoria; Starkhammar, Hans; Börjeson, Sussanne; Kjellgren, Karin; Berterö, Carina
Abstract : Background: Oxaliplatin (OXA) is frequently used in the treatment of patients with colorectal cancer, and OXA-induced neurotoxic side effects are common. Reports on real-time patient-reported neurotoxic side effects and impact on the patient's daily activities are sparse in existing studies. Objective: The aim of this study was to identify and assess patient-reported OXA-induced neurotoxic side effects and their impact on the patient's daily activities, during and after chemotherapy. Methods: In a multicenter prospective longitudinal study, 46 chemo-naïve patients with colorectal cancer treated with postoperative adjuvant OXA-based chemotherapy were monitored during treatment and at 3-, 6-, 9-, and 12-month follow-ups. Patients were recruited from September 2013 to June 2016. In total, 370 Oxaliplatin-Associated Neurotoxicity Questionnaire responses were available for analysis. A mobile phone-based system was used to receive real-time assessments. Results: All patients reported neurotoxic side effects and impact on daily activities during treatment. The side effects changed in character and body location over time and had an impact on the daily activities. Conclusions: The high prevalence of OXA-induced neurotoxic side effects significantly interfered with the patients' daily activities. We found significant differences between baseline data and follow-up time points for neurotoxicity, and the patients had not returned to baseline after 1 year. Implications for Practice: The real-time assessment using mobile phone technology seems to be a valuable tool for monitoring patient-reported neurotoxicity and interventions for tailored care. Effectively identifying neurotoxicity and its impact on the patient's daily activities is important in supportive cancer care.